ДОСЛІДЖЕННЯ ДВОНАПРАВЛЕНОГО ПЕРЕТВОРЮВАЧА З ВИКОРИСТАННЯМ АСИМЕТРИЧНОГО ІНВЕРТОРА З МАГНІТОЗВ‘ЯЗАНИМ ДВООБМОТКОВИМ ДРОСЕЛЕМ В СИСТЕМАХ НАКОПИЧЕННЯ ЕНЕРГІЇ - Мартинов, Д.В.; Руденко, Ю.В.; Мартинов, В.В. (Інститут електродинаміки НАН України, Київ, 2025)
The electromagnetic processes in a bidirectional DC-DC converter using an asymmetric inverter in a battery energy storage system to manage energy flow between sources with different voltage levels are examined. The key advantages of bidirectional converters based on the asymmetric inverter topology are identified. The first advantage is the elimination of through-currents by avoiding combinations of serially connected active power switches during switching intervals. The second advantage is the improved dynamic performance of power switches by using external discrete diodes instead of internal diodes in the switches, significantly reducing the energy dissipated during the reverse recovery process. The article proposes an improvement to the structure of the asymmetric inverter with a magnetically coupled inductor for the bidirectional DC-DC converter through the addition of an extra inductor, which eliminates undesirable circulating currents in the converter that lead to power losses. Analytical expressions are derived for calculating current increments during switching intervals in the magnetically coupled inductor, and the relationship between its inductance and the parameters of the power sources, where circulating currents are absent, is determined. References 16, figures 7.